2013
DOI: 10.1371/journal.pone.0077063
|View full text |Cite
|
Sign up to set email alerts
|

Plasma High Sensitivity Troponin T Levels in Adult Survivors of Childhood Leukaemias: Determinants and Associations with Cardiac Function

Abstract: BackgroundWe sought to quantify plasma high sensitivity cardiac troponin (hs-cTnT) levels, their determinants, and their associations with left ventricular (LV) myocardial deformation in adult survivors of childhood acute leukaemias.Methods and ResultsOne hundred adult survivors (57 males) of childhood acute leukaemias, aged 24.1±4.2 years, and 42 age-matched controls (26 males) were studied. Plasma cTnT was determined using a highly sensitive assay. Genotyping of NAD(P)H oxidase and multidrug resistance prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Abnormal GCS was common in patients treated with anthracycline therapy alone (23%) . Cheung et al and Mavinkurve‐Groothuis et al both showed significant reductions of GCS in patients compared to controls (14% and 30% decrease, respectively). Both Cheung's and Mavinkurve‐Groothius' papers reported significant decreases in GCSr (11% and 19%, respectively).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Abnormal GCS was common in patients treated with anthracycline therapy alone (23%) . Cheung et al and Mavinkurve‐Groothuis et al both showed significant reductions of GCS in patients compared to controls (14% and 30% decrease, respectively). Both Cheung's and Mavinkurve‐Groothius' papers reported significant decreases in GCSr (11% and 19%, respectively).…”
Section: Resultsmentioning
confidence: 96%
“…Cheung et al, Mavinkurve‐Groothuis et al, and Christiansen et al all showed that GLS was significantly reduced in patients vs controls (between 6.4% and ~7.6% decrease). Changes in strain rate were variable: Cheung et al's paper showed no significant change in systolic or diastolic Sr while Mavinkurve‐Groothuis et al's showed a significant 13% decrease in GLSr in patients.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Gender-specific reference values for the paediatric age group remain unavailable. Cheung et al (4) recently reported on elevated highsensitivity cTnT in 19% of the adult survivors associating with an impaired left ventricular function. Despite the fact that they used gender-specific reference values, all their survivors had levels below 14 ng/L, like the patients in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Novel, high-sensitivity methods in the analysis of cardiac troponin T (cTnT) in plasma enable the detection of even subclinical myocardial damage (3,4). Published studies on cardiac troponin among childhood cancer survivors have Abbreviations cTnAAbs, Troponin-specific autoantibodies; cTnI, Cardiac troponin I; cTnT, Cardiac troponin T; MRI, Magnetic resonance imaging; NT-proBNP, N-terminal pro-brain natriuretic peptide; RT3DE, Real-time three-dimensional echocardiography; SD, Standard deviation.…”
Section: Introductionmentioning
confidence: 99%